contestada

What should be the first step to solve the equation?
2x + 9(x - 1) = 8(2x + 2) - 5
O Combine like terms on each side of the equation.
O Use the distributive property on each side of the equation.
Use the subtraction property of equality to subtract 5 from each side of the equation.
Use the addition property of equality to add 2x to each side of the equation.

Respuesta :

Answer:

Your answer would be to Use the distributive property on each side of the equation.

Step-by-step explanation:

You would first expand the equation by using the distributive property on each side of the equation

[tex]2x + 9(x - 1) = 8(2x + 2) - 5\\2x + 9(x) 9(-1) = 8(2x) 8(2) - 5\\2x + 9x-9 = 16x+16 - 5[/tex]

Then you would combine like terms on both sides

[tex]2x+9x-9=11x-9\\16x+16-5=16x+11[/tex]

Now you solve for x

[tex]11x-9=16x+11[/tex]

You subtract 11x from both sides

[tex]11x-9=16x+11\\-11x=-11x[/tex]

Then you subtract 11 from both sides

[tex]-9=5x+11\\-11=-11[/tex]

Then you divide 5 on both sides

[tex]-20=5x[/tex]

[tex]\frac{-20}{5} =\frac{5x}{5}[/tex]

[tex]x=-4[/tex]

ACCESS MORE